Exposure to X-rays Causes Depression-like Behaviors in Mice via HMGB1-mediated Pyroptosis. (15th January 2022) - Xu, Lixing; Huang, Haiqin; Liu, Tianqing; Yang, Tao; Yi, Xuan
Graphical abstract: Highlights: X-rays caused the depression-like behaviors, microglial activation, and neuronal apoptosis in mice. ROS production and overexpression of HMGB1 from neurons participated in radiation-induced brain damage. NLRP3/ASC/Caspase-1-mediated microglial pyroptosis contributed to neuronal damage after X-ray challenge. Abstract: The widespread application of ionizing radiation in industrial and medical fields leads to the increased brain exposure to X-rays. Radiation brain injury (RBI) seriously affects health of patients by causing cognitive dysfunction and neuroinflammation. However, the link between X-ray exposure and depressive symptoms and their detailed underlying mechanisms have not been well studied. Herein, we investigated the potential depression-like behaviors in mice exposed to X-rays and then explored the role of HMGB1 in this injury. We found that X-ray stimulation induced the generation of reactive oxygen species (ROS) in the prefrontal cortex in a dose-dependent manner, leading to the occurrence of depression-like behaviors of the mice. Moreover, X-ray exposure increased the expression of HMGB1, activated NLRP3 inflammasome signaling pathway and microglial cells, and then facilitated the release of pro-inflammatory cytokines, resulting in the pyroptosis and neuron loss both in vivo and in vitro . Additionally, glycyrrhizin (Gly), which is a HMGB1 inhibitor, reversed X-ray-induced behavioral changes and neuronal damage. Our findings indicated that HMGB1-mediated pyroptosis was involved in radiation-induced depression.